Changes in Availability of Oxygen Accentuate Differences in Capsular Polysaccharide Expression by Phenotypic Variants and Clinical Isolates of Streptococcus pneumoniae - Weiser, Jeffrey N. (American Society for Microbiology, 2001)
Most isolates of Streptococcus pneumoniae are mixed populations of transparent (T) and opaque (O) colony phenotypes. Differences in the production of capsular polysaccharide (CPS) between O and T variants were accentuated by changes in the environmental concentration of oxygen. O variants demonstrated a 5.2- to 10.6-fold increase in amounts of CPS under anaerobic compared to atmospheric growth conditions, while CPS production remained low under all conditions for T variants. Increased amounts of CPS in O compared to T pneumococci were associated with increased expression of cps-encoded proteins. The inhibitory effect of oxygen on expression of CPS in O variants correlated with decreased tyrosine phosphorylation of CpsD, a tyrosine kinase and regulator of CPS synthesis. Modulation of CpsD expression and its activity by tyrosine phosphorylation may allow the pneumococcus to adapt to the requirements of both colonization, where decreased CPS allows for adherence, and bacteremia, where increased CPS may be required to escape from opsonic clearance. In patients with invasive infection, paired isolates from the same patient were shown to have predominately a T colony phenotype without phosphotyrosine on CpsD when cultured from the nasopharynx, and an O phenotype that phosphorylates CpsD in response to oxygen when cultured from the blood. Differences in the availability of oxygen, therefore, may be a key factor in allowing for the selection of distinct phenotypes in these two host environments.